An Experimental Study on Combustion and Emission Analysis of Four Cylinder 4-Stroke Gasoline Engine Using Pure Hydrogen and LPG at Idle Condition. (December 2016) - Chitragar, P.R.; Shivaprasad, K.V.; Nayak, Vighnesh; Bedar, P.; Kumar, G.N.
Abstract: Fluctuation in oil prices and stricter exhaust emission norms were the main reasons wakening every researcher to search for suitable and feasible alternative fuels for automotive use. Among the available option gaseous fuels find their best position because of their compatible physical-chemical properties and ecofriendly nature than present fossil fuels. Hydrogen's combustion properties like high energy content, high heating value, wide range of flammability and low ignition energy with almost least toxic emissions are favorable to use in an IC engine as an alternative fuel. Liquid petroleum gas (LPG) has lower carbon content, higher calorific value, octane number and flame propagation speed will improve the emission results compared to gasoline fuel. This paper describes an experimental results carried out to evaluate the combustion and emission performance of a Maruti Suzuki make, spark ignited four cylinders, four stroke engines at idle condition by using pure hydrogen, LPG and gasoline. The engine was adjoined with Electronic Control Unit (ECU) assisting hydrogen and LPG injector system keeping gasoline line unchanged. Tests were carried out by using compressed hydrogen gas regulated by two stage pressure reduction from cylinder to atmospheric value and by using vaporizer pressure for LPG. For comparison engine was run first by gasoline and then by pure hydrogen and LPG. Study revealed that there was increment of 13% cylinder pressure for pure hydrogen and decrement of 4.5% cylinder pressure for LPG when compared to gasoline. The burn duration for pure hydrogen, LPG and gasoline were found to be increasing respectively which infers that hydrogen has very short combustion duration and gasoline higher. It was observed that toxic emissions like Carbon monoxide (CO), Hydrocarbons (HC) and Oxides of Nitrogen (NOx ) were improved for pure hydrogen than LPG and gasoline.